Utilização de rádio frequência para telemetria de motores automotivos - Ferreira, Breno Mendes (2015)
The process of research, development and improvement in data communication techniques are some of the most important points that ensure the reliability and performance of automotive engine, results of a more advanced automation control. The advancement of technology has brought the integration of electronics with the automotive engine which acts in order to bring more efficiency, comply with international standards of emissions and still ensure the perfect operation of the engine, taking into account data from electronic sensors, both in engine as the external environment. To improve this integration is required an automotive telemetry system for analysis, study and processing of vehicle data on operating. This study aimed to develop a prototype device capable of reading and acting in the automotive network remotely by a mobile device, providing short-range telemetry solution. The prototyping is held on development platforms of microcontrollers Tower of Freescale, with communication converter with CAN network. Wireless communication is obtained by Bluetooth UART device. And, to validate this work was used telemetry to generate graphics in real time, in Matlab software and the development of an Android application to read and write commands acting on the CAN network. As a result was obtained only sending data needed for specific applications, for thus does not overload the data processing on mobile devices carrying out the telemetry.